UJI KERENTANAN NYAMUK Aedes aegypti TERHADAP LAMDA SIHALOTRIN DAN SIPERMETRIN TAHUN 2016 - Yulistra Naftali Eka Putra; Koerniasari .; Mamik . (GEMA LINGKUNGAN KESEHATAN, 2016)
Dengue Hemorrhagic Fever (DHF) in Indonesia is an endemic disease with morbidity level tends to increase from year to year and extends to 400 regencies/cities from 474 regencies/cities in Indonesia. This disease even frequently causes Outbreaks (KLB). One of the dengue controls is chemical control. Chemical control by using insecticides is the most popular form of control in the society because it is easy to implement. Insecticides are most commonly used are lambda cyhalothrin and sipermetrin because it is cheap and readily available. The use of the same insecticide for around 2-20 years and improper dosage can cause mosquitoes to become resistant. This study aimed to test the susceptibility of mosquitoes to Lamdacyhalothrin and cypermethrin. This research was experimental and the study design used "with Pretest-Posttest Control Group". Susceptibility Test used 500 Aedesaegypti mosquito as sample and using 20 tubes with ach tube is filled 25 mosquitoes. 0.05% of Lamdacyhalothrin and 0.05% of cypermethrin were put in 8 tubes while for control was 4 tubes containing plain white paper. Mosquitoes were exposed for 1 hour, then transferred into paper cup containing cotton containing sugar water, then stored for 24 hours. The observation was then carried out and calculating the percentage of dead mosquitoes. The results showed the number of dead mosquitoes with Lamdacyhalothrin was 7%, included in the category of resistance (WHO). The number of dead mosquitoes with cypermethrin was 2.5% which is also in the category of resistance. This susceptibility status categories are taken based on the criteria of the WHO, the mortality 80% means resistant, the mortality of 80-97% are tolerant, and 98% - 100% is susceptible (WHO, 1975) The society is advised  to use insecticide in the right dose, limiting the excessive use of insecticides and if necessary, only to use non-chemical control.  Keywords : Aedes aegypti, Suceptibility Test, Lamdacyhalothrin, Cypermethrin